Peran Perempuan dan Keluarga Katolik di Era Disrupsi Teknologi di Bali Pada Masa Pandemi Covid-19 - Sunaryo, Fransiska Dewi Setiowati; Ayu Rai Wahyuni, Anak Agung (Humanis; Vol 26 No 3 (2022), 2022)
The role of women cannot be denied having a big role in maintaining family integrity in the era of technological disruption. The era where internet technology is growing very rapidly through social media and entertainment. Women who have often played the number two role, can now play a dual role when dealing with the era of disruption coupled with the COVID-19 pandemic that hit almost all over the world, including Bali in particular. This study of the role of women is interesting because not many have raised it if it is based on the teachings of the Catholic religion which has recognized the position of women in the eyes of the Catholic Church since the Second Vatican Council in 1960. The issues raised in this paper include the role of mothers and Catholic families in the era of technological disruption and the role of the Catholic Church in dealing with the concerns of its people in the midst of the COVID-19 pandemic in Bali. The theory used is a sociological approach about dual roles. The research method used is a qualitative research method using library sources and in-depth interviews with informants using snowball sampling technique.